2022
DOI: 10.3390/tomography8040169
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection with mpMRI According to PI-RADS v2 Compared with Systematic MRI/TRUS-Fusion Biopsy: A Prospective Study

Abstract: Background: mpMRI assesses prostate lesions through their PI-RADS score. The primary goal of this prospective study was to demonstrate the correlation of PI-RADS v2 score and the volume of a lesion with the presence and clinical significance of prostate cancer (PCa). The secondary goal was to determine the extent of additionally PCa in inconspicuous areas. Methods: All 157 patients underwent a perineal MRI/TRUS-fusion prostate biopsy. Targeted biopsies as well as a systematic biopsy were performed. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Modern prostate biopsy techniques are based on the computerised 3D merging of the ultrasound and MRI images to provide better vision during the procedure (Fusion Biopsy) [ 9 , 10 ]. However, the method is expensive due to high equipment costs.…”
Section: Introductionmentioning
confidence: 99%
“…Modern prostate biopsy techniques are based on the computerised 3D merging of the ultrasound and MRI images to provide better vision during the procedure (Fusion Biopsy) [ 9 , 10 ]. However, the method is expensive due to high equipment costs.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of the lesions was significantly correlated with ISUP grades. The authors concluded that the PI-RADS v2 score and lesion volume were associated with the presence and clinical significance of prostate cancer, but that there was not an insignificant number of false positive findings [ 4 ].…”
mentioning
confidence: 99%